Conditional expectations and martingales in noncommutative Lp-spaces associated with center-valued traces - GANIEV, Inomjon G.; Mukhamedov, Farrukh M. (Elsevier BV, 2017)
In this paper we prove the existence of conditional expectations in the noncommutative Lp(M,Φ)-spaces associated with center-valued traces. Moreover, their description is also provided. As an application of the obtained results, we establish the norm convergence of weighted averages of martingales in noncommutative Lp(M,Φ)-spaces.